Building National Character through Religion-Based Educational Sciences - Sururin, Sururin; Ramadhan, Yokha Latief; Syauqii, Fachri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The philosophy of education in general is often restricted to the memorization or mere introduction of values, without progressing to the stage of internalizing these values as individual commitments in everyday life. This study seeks to analyze the concept of educational philosophy and sciences from the perspective of K.H. Hasyim Asy’ari and to evaluate its relevance in the digital era. Methodology: This research adopts a literature-based approach, applying content analysis and descriptive methods within the framework of educational sciences. Both primary and secondary sources, including books and journal articles, were employed to investigate K.H. Hasyim Asy’ari’s philosophy of education. Main Findings: The findings demonstrate that K.H. Hasyim Asy’ari’s philosophy of education, particularly in the Islamic educational sciences context, emphasizes the formation of holistic human beings. Such individuals embody a balanced integration of faith and knowledge, possess advanced scientific competence, exhibit mental resilience, and maintain strong social character within the family, school, and broader community. Novelty/Originality of this study: K.H. Hasyim Asy’ari’s educational philosophy and sciences is highly relevant to be internalized in the digital era. It provides a comprehensive framework for nurturing individuals who are adaptive to rapid technological and societal changes while remaining steadfast in upholding noble moral values.